Experimental and numerical study on mating operation of a topside module by a floating crane vessel in waves. (15th April 2018) - Ha, Y.J.; Nam, B.W.; Hong, S.Y.; Jung, D.W.; Kim, H.J.
Abstract: In this study, an experimental and numerical study was conducted for investigating the mating operations of a topside module onto a FLNG by using a floating crane in waves. A series of model tests were performed in Ocean Engineering Basin at KRISO with a model set-up of 1:45 scale ratio. The floating crane vessel was equipped with a crane system and dynamic positioning system. The topside module was simplified as a rectangular box of about 2000 Tonf. Four leg mating units(LMUs) were introduced to model the interface units between the FLNG and the topside module. While the interaction forces between the crane vessel and the topside module are transferred via the crane wires, the topside module interacts with the FLNG through the LMUs. Experimental conditions include four different mating stages, i.e. 0%, 20%, 50% and 93% load transfers, under regular and irregular wave conditions. To validate the experimental data, a time-domain numerical simulation method is applied to solve the coupled dynamics of three bodies. The discussions were made on three main points. First, the motion characteristics of the lifted object as well as the crane vessel were investigated by comparing the simulation results. Second, the dynamic tensions of the crane wires were evaluated under the various wave and mating conditions. Final discussion was made on the LMU impact forces. Highlights: Experimental study for the mating operations of a topside module by a floating crane vessel in waves. Time-domain simulation for the fully coupled dynamics of three bodies including hydrodynamic & mechanical interactions. Focus on motion characteristics of the lifted module, the dynamic wire tensions and reaction forces on LMUs.